Disarranged neuroplastin environment upon aging and chronic stress recovery in female Sprague Dawley rats. (14th May 2021) - Balog, Marta; Blažetić, Senka; Ivić, Vedrana; Labak, Irena; Krajnik, Bartosz; Marin, Raquel; Canerina‐Amaro, Ana; de Pablo, Daniel Pereda; Bardak, Ana; Gaspar, Robert; Szűcs, Kálmán Ferenc; Vari, Sandor G.; et al.
Abstract: Chronic stress produces long‐term metabolic changes throughout the superfamily of nuclear receptors, potentially causing various pathologies. Sex hormones modulate the stress response and generate a sex‐specific age‐dependent metabolic imprint, especially distinct in the reproductive senescence of females. We monitored chronic stress recovery in two age groups of female Sprague Dawley rats to determine whether stress and/or aging structurally changed the glycolipid microenvironment, a milieu playing an important role in cognitive functions. Old females experienced memory impairment even at basal conditions, which was additionally amplified by stress. On the other hand, the memory of young females was not disrupted. Stress recovery was followed by a microglial decrease and an increase in astrocyte count in the hippocampal immune system. Since dysfunction of the brain immune system could contribute to disturbed synaptogenesis, we analyzed neuroplastin expression and the lipid environment. Neuroplastin microenvironments were explored by analyzing immunofluorescent stainings using a newly developed Python script method. Stress reorganized glycolipid microenvironment in the Cornu Ammonis 1 (CA1) and dentate gyrus (DG) hippocampal regions of old females but in a very different fashion, thus affecting neuroplasticity. The postulation of four possible neuroplastin environments pointed to the GD1a ganglioside enrichment during reproductive senescence of stressed females, as well as its high dispersion in both regions and to GD1a and GM1 loss in the CA1 region. A specific lipid environment might influence neuroplastin functionality and underlie synaptic dysfunction triggered by a combination of aging and chronic stress. Abstract : Stress causes memory decline in (pre)menopausal female rats. This effect was followed by expressional changes in the lipid environment of the APP, Np65, AMPA‐R, glial cell number and structural changes of membrane lipids in hippocampus. We postulated four possible Np65 environments involving GD1a enrichment and its high dispersion. The specific lipid environment might influence Np65 functionality and could underlie synaptic dysfunction and amyloidogenesis upon aging and stress.